International ambidexterity and innovation performance: The moderating role of the host country's institutional quality - Peng Xiao; Haiyan Zhang; Xiaoxia Sun; Feng Zhang; Xiaoyan Du; Guoxin Liu (Journal of Innovation & Knowledge (JIK), 2022)
Organizational ambidexterity has been employed in the study of international business. Existing studies advocate an ambidextrous internationalization strategy for multinational enterprises in emerging markets (EM MNEs). However, the performance effect and moderating mechanism of international ambidexterity have not been fully explored yet. This study expands the combinative view of organizational learning and institutional perspective, and examines the impact and moderating mechanism of international ambidexterity on firm performance based on 387 Chinese multinationals. This study adopts the questionnaire survey method to obtain the research sample and tests the relationships among variables through multiple regression analysis. The conclusions indicate that both the balanced and combined dimensions of international ambidexterity positively impact innovation performance. Additionally, EM MNEs operating in countries with well-developed institutions are more innovative than those operating in countries with underdeveloped institutions. This study not only promotes the development of internationalization and institutional theories but also guides managers of EM MNEs to formulate internationalization strategies.
Keywords: 650; Institutional quality; Innovation performance; AFGMOP; Classification codes; Exploitation; Exploration; International ambidexterity